2009
DOI: 10.1002/path.2525
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of tight junctions during polymicrobial sepsis in vivo

Abstract: The disruption of intestinal epithelial tight junctions may result in barrier function dysfunction during polymicrobial sepsis. The pathophysiology of sepsis involves breakdown of barrier integrity, which correlates with adverse outcome during sepsis. However, the mechanisms underlying loss of barrier function in sepsis remain unknown. In the present study in mice, tight junction (TJ) structure was analysed by transmission electron microscopy; intestinal permeability was assessed using molecular tracer measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 28 publications
9
66
0
2
Order By: Relevance
“…Our results are in line with studies in mouse sepsis models, which also show marked reductions in occludin and claudin 5 levels (36,37). Studies in septic mice have also shown decreased ZO-1 expression and disorganized patterning with greater fragmentation, similar to our findings in the zebrafish sepsis model (38).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are in line with studies in mouse sepsis models, which also show marked reductions in occludin and claudin 5 levels (36,37). Studies in septic mice have also shown decreased ZO-1 expression and disorganized patterning with greater fragmentation, similar to our findings in the zebrafish sepsis model (38).…”
Section: Discussionsupporting
confidence: 82%
“…Studies in septic mice have also shown decreased ZO-1 expression and disorganized patterning with greater fragmentation, similar to our findings in the zebrafish sepsis model (38). We also saw upregulation of claudin 2 expression, pore forming tight junction protein, known to be markedly upregulated in mouse polymicrobial sepsis models (37). Interestingly, we did not detect any significant differences in VE cadherin expression, though this AJ protein is widely implicated in regulating endothelial integrity and permeability.…”
Section: Discussionsupporting
confidence: 77%
“…A decrease in TER may be induced by claudin-1 disruption or downregulation (44). Claudin-1 has been shown to be aberrantly localized in response to infection by a variety of pathogens (13,21,44). We observed that monolayers infected with EAEC 042 or JM221 caused a dissociation of claudin-1 from the tight junctions (Fig.…”
Section: Vol 78 2010 Eaec Disrupts Epithelial Cell Tight Junctions mentioning
confidence: 59%
“…Tight junctions are part of specialized lipid raft-like membrane microdomains (Nusrat et al, 2000). It was recently shown that sepsis causes redistribution of tight junctions in membrane microdomains and that this redistribution is responsible for increased permeability (Li et al, 2009). Mucosal scrapings from the ileum were homogenized and separated by ultracentrifugation.…”
Section: Mmp13 Contributes To Tight Junction Destabilizationmentioning
confidence: 99%